Thermal analysis of eyring-powell hybrid nanofluid: A case of combined convective transport and radiative heat flux along inclined stretching/shrinking sheet - Aljabali, Ahlam; Abdul Rahman, Mohd Kasim; Iskandar, Waini; Najiyah Safwa, Khashi’ie; Tijani, Yusuf Olatunji (World Scientific and Engineering Academy and Society, 2025)
Hybrid nanofluids are designed to improve conventional nanofluids' stability and other thermal properties. The present work investigates the flow of combined convective transport and the influence of radiation on the studied flow. A hybrid nanofluid (Cu - Al2O3/water) flows through a vertically inclined stretching/shrinking sheet. To simplify the governing equations, the deterministic two-variable differential equations (PDEs) are systematically transformed into a system of one-variable differential equations by using appropriate similarity transformations. The bvp4c function of the MATLAB program is also used to solve the simplified mathematical model. The present study investigates and presents in tabular and graphical form the effects of stretching/shrinking surfaces, suction, and volume fraction of the nanoparticles on the velocity and temperature profiles as well as on the engineering quantities. The present results are first validated and confirmed as acceptable before the full calculations are performed. Overall, the results of this study show that the investigated parameters influence the flow characteristics, which can serve as a controlling factor for heat transfer.